TEACHER’S DIRECTIVE SPEECH ACT IN ONLINE TAMIL LANGUAGE TEACHING - Manoqaran, Vikneshwary; Ramalingam, Selvajothi (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
The COVID-19 pandemic brought a rapid shift to online learning, changing the way languages are taught in primary schools. This study looks at how Tamil language teachers in Tamil National Type Primary Schools (SJKT) in the Klang district use directive speech acts during online instruction. To explore this, one hour online lessons were recorded from five randomly chosen schools and analyzed using Ervin-Tripp’s categorization framework. A total of 963 directive speech acts were identified. The analysis shows that imperatives were by far the most common (74.8%), followed by question directives (24.6%), while embedded imperatives and need statements appeared only occasionally. Attention getting directives were used frequently, helping teachers maintain focus and move smoothly between activities. The study also found variation across schools, suggesting that individual teaching styles and interactional dynamics strongly shape online communication. Overall, the findings point to the importance of clear and directive communication in sustaining student engagement and managing virtual classrooms, and they offer insights for improving first-language instruction in digital settings.